1994
DOI: 10.1093/cercor/4.3.260
|View full text |Cite
|
Sign up to set email alerts
|

Induced Microgyria and Auditory Temporal Processing in Rats: A Model for Language Impairment?

Abstract: Studies have shown the existence of minor developmental cortical malformations, including microgyria, in the brains of dyslexics. Concomitant studies have shown that language-impaired individuals exhibit severe deficits in the discrimination of rapidly presented auditory stimuli, including phonological and nonverbal stimuli (i.e., sequential tones). In an effort to relate these results, male rats with neonatally induced microgyria were tested in an operant paradigm for auditory discrimination of stimuli consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 40 publications
11
70
1
1
Order By: Relevance
“…A focal freezing lesion administered on postnatal day 1 in the rat (when neurons are still migrating in the cortex) results in 4-layered neocortical microgyria, similar to those found in humans with dyslexia (Fitch et al, ,1994. Several investigators have found that rats with induced cerebrocortical microgyria are impaired on rapid auditory processing tasks, both as mature animals (Clark et al, 2000Herman et al (1997) and across development Peiffer et al, 2004).…”
Section: Animal Studiesmentioning
confidence: 72%
See 1 more Smart Citation
“…A focal freezing lesion administered on postnatal day 1 in the rat (when neurons are still migrating in the cortex) results in 4-layered neocortical microgyria, similar to those found in humans with dyslexia (Fitch et al, ,1994. Several investigators have found that rats with induced cerebrocortical microgyria are impaired on rapid auditory processing tasks, both as mature animals (Clark et al, 2000Herman et al (1997) and across development Peiffer et al, 2004).…”
Section: Animal Studiesmentioning
confidence: 72%
“…Processing of rapid, successive auditory stimuli has also been studied in rodents using both electrophysiological and behavioural paradigms (Fitch et al, 1994;Frenkel et al, 2000;Friedman et al 2004;Peiffer et al, 2004). Of course, animal models enable researchers to investigate the effects of induced lesions and malformations in a manner not possible with humans.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Therefore, some authors concluded that the laterality effect is related to the communicative valence of signals rather than to their acoustic characteristics (36). Studies applying different artificial, semantically neutral sounds, only occasionally performed in animals (Table S1), yielded inconsistent results (34,(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…Miller and Tallal (1996) make this claim: '[W]e believe that we have identified an underlying neurological impairment that disrupts temporal processing rates in the brains of language learning impaired individuals ' (p. 8). Taken together with the suggestion that the problems dyslexics have can be traced back to anomalies in the magnocellular system (Livingstone, Rosen, Drislane & Galaburda, 1991;Galaburda, Menard, & Rosen, 1994;Fitch, Tallal, Brown, Galaburda, & Rosen, 1994), we discern the following implicit chain of causes in Tallal's and her colleagues' reasoning: (1) Neurological impairment leading to (2) anomalies in temporal processing leading to (3) auditive anomalies leading to (4) phonological anomalies leading to (5) language and cognitive problems. As we see their work, only the first link in this chain, the neurological impairment, is purely biological.…”
Section: Symptomsmentioning
confidence: 72%